Two regimes of confinement in tension: partial prison reform in the Dominican Republic - Peirce, Jennifer (Carceral communities in Latin America, 2021)
The Dominican Republic created a new prison system in 2003, with new buildings, staff, and programs and a human rights ethos. It now holds a third of prisoners and operates in parallel with the “traditional” penal regime. The new system can be materially more comfortable for some, but can be more restrictive for others. In dialogue with Birkbeck’s concept of “regimes of confinement,” this chapter describes key facets of each regime and explores prisoners’ perceptions of the advantages and drawbacks of each. This chapter interrogates assumptions about standards and rights inside prisons, particularly in settings with severe inequality and constrained resources. The Dominican example illustrates the benefits and unintended consequences of progressive prison reforms and offers insights into what matters most to prisoners.